Transformasi Digital: Pelatihan E-Commerce untuk Meningkatkan Wirausaha di Villa Mutiara Serpong - Agus Sriyanto; Yugi Setyarko; Teja Endra Eng Tju; Rina Ayu Vildayanti; Astrid Dita Meirina Hakim; Aris Wahyu Kuncoro (Universitas Kristen Indonesia Toraja, 2024)
The Villa Mutiara Serpong Pondok Jagung Complex is a dynamic environment with various social activities involving all community groups. This Community Service Activity (PKM) aims to improve the entrepreneurial spirit of citizens through e-commerce training. The methods used include identifying needs, planning and implementing training programs, and evaluating results. The training carried out covers the basic principles of e-commerce, the implementation process, utilization of the marketplace, and use of social media for product promotion. The results show an increase in citizens' understanding and skills in e-commerce, which has the potential to improve local business development and community welfare.